Pengaruh Level Pemberian Duckweed (Lemnacea) Terfermentasi terhadap Kecernaan dan Kualitas Telur Burung Puyuh (Coturnix-coturnix Japonica): Effect of Fermented Duckweed (Lemnacea) Meal Feeding Levels on Nutrient Digestibility and Egg Quality of Quail (Coturnix-coturnix Japonica) - Al Ayuni, Yusfi; Muflihun, Sadiqin (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
This study aimed to evaluate the levels of fermented duckweed meals in the quail's diet on nutrient digestibility and egg quality. A total of 100 two-month-old quails were randomly placed into four different diet groups. The experiment used a Completely Randomized Design. A feeding trial was conducted for 6 weeks and 1-week adaptation. The levels of fermented duckweed meal used were P0 = 0% (control), P1 = 5%, P2 = 10%, and P3 = 15%. Egg samples were collected during the final week to measure egg quality parameters, including egg weight, yolk weight, albumen weight, shell weight, yolk color, and haugh Unit (HU). Nutrient digestibility observed includes organic matter, crude fat and crude protein. Data was analyzed using ANOVA and followed by Duncan's multiple range test. The results showed that the inclusion of fermented duckweed meals significantly affected (p<0.05) egg weight, egg yolk weight, haugh unit and organic matter digestibility, crude fat digestibility but did not significantly affect egg white weight, shell weight, egg yolk color, HU and protein digestibility. The P1 5% treatment gave the highest results on egg weight, HU, organic matter digestibility, fat digestibility and protein digestibility, while an increase in the level of 15% (P3) reduced egg weight, yolk weight, egg white weight, HU, organic digestibility and fat digestibility. In conclusion, the levels of 5% and 10% of fermented duckweed meal showed optimum effects for improving egg quality and nutrient digestibility in quail.